2006
DOI: 10.1038/sj.bjp.0706843
|View full text |Cite
|
Sign up to set email alerts
|

Delphinidin and cyanidin inhibit PDGFAB‐induced VEGF release in vascular smooth muscle cells by preventing activation of p38 MAPK and JNK

Abstract: Background and purpose: Red wine polyphenols (RWPs) inhibit the expression of vascular endothelial growth factor (VEGF), a major pro-angiogenic and pro-atherosclerotic factor, in vascular smooth muscle cells (VSMCs). The aim of this study was to identify which red wine polyphenols were inhibitory and to determine the mechanism underlying the inhibitory effects. Experimental approach: Release of VEGF stimulated by platelet derived growth factor AB (PDGF AB ) , from human aortic VSMCs was measured by immunoassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…The results of the present study demonstrated that the anti-inflammatory effect of delphinidin reduced the p-p38-MAPK protein expression and caspase-3 activity in a rat model of SCI. Furthermore, Oak et al (30) reported that delphinidin prevents the activation of p38-MAPK and JNK in vascular smooth muscle cells. Overall, these data suggest that administration of delphinidin alleviates the SCI-induced inflammation through suppression of the p38-MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrated that the anti-inflammatory effect of delphinidin reduced the p-p38-MAPK protein expression and caspase-3 activity in a rat model of SCI. Furthermore, Oak et al (30) reported that delphinidin prevents the activation of p38-MAPK and JNK in vascular smooth muscle cells. Overall, these data suggest that administration of delphinidin alleviates the SCI-induced inflammation through suppression of the p38-MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A compound with four hydroxyl groups (3, 3′, 4′ and 5′), delphinidin has recently been shown to be a potent inhibitor of vascular endothelial growth factor receptor activity (Lamy et al, 2006). The presence of vicinal hydroxyl substituents on the B-ring of delphinidin seems to be crucial for interaction with EGFR, as tyrosine kinase activity associated with this cell surface receptor is inhibited by delphinidin in human breast cancer cells (Oak et al, 2006). This is significant as inhibition of downstream effectors of the activated receptors by delphinidin may disturb vital biological cues and hinder the progression of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanidin is demonstrated to be beneficial against diabetes [4,5], cancer [6][7][8], and atherosclerosis [9]. In the central nervous system, recent investigations indicate that cyanidin showed potential protections against Alzheimer's disease and multiple sclerosis [10,11].…”
Section: Introductionmentioning
confidence: 99%